A smart phone-based system for post-earthquake investigations of building damage. (March 2018) - Xu, Zhen; Lu, Xinzheng; Cheng, Qingle; Guan, Hong; Deng, Li; Zhang, Zongcai
Abstract: Current post-earthquake investigations of building damage are mainly conducted manually, making the collection and management of the investigation data inefficient. To overcome this shortcoming, a professional system for post-earthquake investigations of building damage is proposed herein using smart phones. This system adopts a framework which uses smart phones for distributed data collection and a web browser for centralized data management. A building-oriented database is designed to satisfy the requirements of data organization in the investigations. In addition, a data exchange mechanism between smart phones and the web server is created, demonstrating a satisfactory level of fault-tolerance for various use cases of the system. Further, an algorithm of reverse address retrieval of photos based on multi-threads is designed to conveniently index photos by their addresses. The proposed system is used in a virtual investigation of Tsinghua University campus and a practical investigation of the Tibet area during the 2015 Nepal earthquake. These case studies demonstrate that the proposed system offers an intelligentized, efficient and networked tool for post-earthquake investigations of building damage.